FUNGSI PERTUNJUKAN TARI JEPIN TALI BINTANG PADA MASYARAKAT DESA KALIMAS KABUPATEN KUBU RAYA - Porwini, Yefi; Fretisari, Imma; Silaban, Chiristian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis research was aimed to describe, give the comprehension and knowledge about the function of performing and study implementation of Jepin Tali Bintang in Kubu Raya. This research used qualitative descriptive method. Anthropology also was used in this research. The research data was the function of Jepin Tali Bintang dance performance to the society of Kalimas village, Kubu Raya regency. The informants in the observation in this research were Juhermi Thair, Muhammad Yusuf Dahyani, and Jhohor Yahya). The technique of data collection were observation, interview, and documentation. The tool of data collections are the interview sheets, record book, interview guidance, and a phone camera. Based on the data analysis, it could be concluded that Jepin Tali Bintang dance in Kubu Raya had the functions in human life. They are as social function, entertainment, and aesthetical performance. The result of this research that was expected to be implemented on Cultures and Arts lesson in the first semester of the tenth grade.Â Keywords: Dance functions, Jepin Tali Bintang dance.